2013
DOI: 10.1159/000354446
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharides Shapes the Human Wharton's Jelly-Derived Mesenchymal Stem Cellsin Vitro

Abstract: Background: Although the expression of toll-like receptors (TLRs) on different types of human mesenchymal stem cells (hMSCs) has recently been reported, controversy remains regarding the presence of TLR4 as well as its engagement and impact on human Wharton's jelly-derived MSCs (hWJ-MSCs). Methods: In the present study, the expression and role of TLR4 in hWJ-MSCs was investigated using a model of lipopolysaccharide (LPS). Proliferation, apoptosis, and the expression of paracrine factors in hWJ-MSCs primed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 42 publications
(80 reference statements)
2
9
0
Order By: Relevance
“…Finally, we evaluated protein and mRNA expression in nonstimulated MSC and after LPS and/or IFN γ treatment, in order to understand how their regulatory function could be affected. As previously described, we found a slight increase in the mRNA of the proinflammatory cytokines TNF- α and IL-6, along with a significant increase in the chemotactic IL-8 [ 23 – 29 ] and the immunosuppressor IDO, ICOSL, and CD73 [ 26 , 30 , 31 ], upon stimulation with LPS + IFN γ . Of note, an increased expression of other immunoregulatory molecules, such as fibroblast growth factor 2 (FGF2), hepatocyte growth factor (HGF), cyclooxygenase 2 (COX2), prostaglandin E2 (PGE2), upon TLR4 stimulation had also been described in the literature [ 26 , 28 , 32 , 33 ].…”
Section: Discussionsupporting
confidence: 67%
“…Finally, we evaluated protein and mRNA expression in nonstimulated MSC and after LPS and/or IFN γ treatment, in order to understand how their regulatory function could be affected. As previously described, we found a slight increase in the mRNA of the proinflammatory cytokines TNF- α and IL-6, along with a significant increase in the chemotactic IL-8 [ 23 – 29 ] and the immunosuppressor IDO, ICOSL, and CD73 [ 26 , 30 , 31 ], upon stimulation with LPS + IFN γ . Of note, an increased expression of other immunoregulatory molecules, such as fibroblast growth factor 2 (FGF2), hepatocyte growth factor (HGF), cyclooxygenase 2 (COX2), prostaglandin E2 (PGE2), upon TLR4 stimulation had also been described in the literature [ 26 , 28 , 32 , 33 ].…”
Section: Discussionsupporting
confidence: 67%
“…Studies have shown that the immunomodulatory property of MSCs seems to depend on their origin, as differences between bone marrow, adipose tissue, and Wharton's jelly-derived MSCs were found recently [48, 49]. These studies demonstrated the resistance of Wharton's jelly-derived MSCs to bacterial challenge compared to other postnatal sources of MSCs.…”
Section: Discussionmentioning
confidence: 92%
“…6,7 In recent years, a number of pre-conditioning strategies have been used to boost MSC function and therapeutic potential. Such strategies include treatment with growth factors, 8,9 cytokines, [10][11][12] hypoxic shock, 13 HDLs, 14 lipopolysaccharide (LPS) 15 or chemical compounds. 16,17 Based on findings from these studies, pre-treatment greatly enhances cell survival and the potential to migrate to damaged or inflamed tissues, thereby markedly improving the efficacy of these cells in the treatment of certain diseases or in tissue repair in an injury-specific fashion.…”
Section: 2mentioning
confidence: 99%